2010
DOI: 10.4143/crt.2010.42.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and Metastatic Trichilemmal Carcinoma of the Skin Over the Thigh: A Case Report

Abstract: I n t r o d u c t i o nTrichilemmal carcinoma (TC) is a rare malignant tumor that develops from the external root sheath of the hair follicle. It usually is found in the skin of the face or ears of elderly women on areas that are exposed to the sun, and TC generally has an indolent clinical course (1,2). This condition is usually curable after a wide excision (2). TC must be differentiated from other skin abnormalities such as squamous cell carcinoma, basal cell carcinoma, keratoacanthoma, and invasive Bowen's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 11 publications
(12 reference statements)
3
21
0
1
Order By: Relevance
“…The previous largest study including 26 cases of trichilemmal carcinoma showed that the overall 5-year survival rate reached 89.2% and many studies documented positive outcomes by a wide surgical excision of the primary lesion [6e8]. On the other hand, recurrence or metastasis has seldom been reported in the literature and only three cases of metastasis of trichilemmal carcinoma were reported and their prognosis was poor as same as our case [6,9]. Although transplant recipients receiving immunosuppressants are at a high risk of cancer, our case is the first case of trichilemmal carcinoma in transplant patients with aggressive tumor characteristics.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The previous largest study including 26 cases of trichilemmal carcinoma showed that the overall 5-year survival rate reached 89.2% and many studies documented positive outcomes by a wide surgical excision of the primary lesion [6e8]. On the other hand, recurrence or metastasis has seldom been reported in the literature and only three cases of metastasis of trichilemmal carcinoma were reported and their prognosis was poor as same as our case [6,9]. Although transplant recipients receiving immunosuppressants are at a high risk of cancer, our case is the first case of trichilemmal carcinoma in transplant patients with aggressive tumor characteristics.…”
Section: Discussionsupporting
confidence: 58%
“…Considering the rapid firing multiple metastases, the benefits of surgical resections for metastatic lesions of trichilemmal carcinoma in the present case were uncertain, although the surgical resection represents an important therapeutic approach for other cancers that lack effective systemic treatment. In previous reports about metastatic trichilemmal carcinoma, cisplatinbased regimens were often used resulting in tumor growth control [6,9,13].…”
Section: Discussionmentioning
confidence: 99%
“…They both had an invasive tumor. Although There are some reports of metastatic cases and death from these tumors in the literature, the invasion of the dura is very rare [1,5,6]. The first case had dural invasion, which required dural reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors arise mainly in areas of dense hair follicle concentration: 90% occur on the scalp [1]. The usual clinical presentation is a subcutaneous cystic nodule.…”
Section: Introductionmentioning
confidence: 99%
“…For example digital papillary adenocarcinoma (DPAC) has a 50% recurrence rate, with a 14% risk of metastasis (especially to lung),8 sebaceous carcinoma (SC) shows an overall 25% risk of lymph node or distant metastasis,9 and porocarcinoma is reported to have a 20% risk of local recurrence and metastatic rate 10 11. Meanwhile, some other malignant adnexal tumours, such as trichilemmal carcinoma, have a very low, if any, metastatic potential 12. Therefore, the correct classification of these tumours has a paramount significance in determining the patient's long-term survival and follow-up.…”
Section: Introductionmentioning
confidence: 99%